The relationship between menopausal status and different histopathological pictures among 300 Indonesian females with breast cancer - Soetrisno, Esti; Tjahjadi, Gunawan; Sakamoto, Goi; Roostini, Endang S.; Cornain, Santoso; Tjindarbumi, Didid; Ramli, Muchlis; Darwis, Idral; Prihartono, Joedo; Ohno, Yoshiyuki; Budiningsih, Setyawati; Wakai, Kenji (Medical Journal of Indonesia, 1999)
[no abstract available]